2019
DOI: 10.3389/fnhum.2019.00172
|View full text |Cite
|
Sign up to set email alerts
|

Current State and Future Prospects of EEG and fNIRS in Robot-Assisted Gait Rehabilitation: A Brief Review

Abstract: Gait and balance impairments are frequently considered as the most significant concerns among individuals suffering from neurological diseases. Robot-assisted gait training (RAGT) has shown to be a promising neurorehabilitation intervention to improve gait recovery in patients following stroke or brain injury by potentially initiating neuroplastic changes. However, the neurophysiological processes underlying gait recovery through RAGT remain poorly understood. As non-invasive, portable neuroimaging techniques,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 81 publications
0
52
0
Order By: Relevance
“…Regarding the cortical correlates of walking, numerous studies identified either increaesed oxygenated hemoglobin (Hboxy) concentration changes in the sensorimotor cortex (SMC) by using fNIRS [53, 5759] or suppressed alpha and beta power in sensorimotor areas by using electroencephalography (EEG) [6062] demonstrating that motor cortex and corticospinal tract contribute directly to the muscle activity of locomotion [63]. However, brain activity during RAW [36, 61, 6468], especially in patients [69, 70] or by using fNIRS [68, 69], is rarely studied [71].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the cortical correlates of walking, numerous studies identified either increaesed oxygenated hemoglobin (Hboxy) concentration changes in the sensorimotor cortex (SMC) by using fNIRS [53, 5759] or suppressed alpha and beta power in sensorimotor areas by using electroencephalography (EEG) [6062] demonstrating that motor cortex and corticospinal tract contribute directly to the muscle activity of locomotion [63]. However, brain activity during RAW [36, 61, 6468], especially in patients [69, 70] or by using fNIRS [68, 69], is rarely studied [71].…”
Section: Introductionmentioning
confidence: 99%
“…To summarize, previous studies mostly focused the effects of RA on either gait characteristics or brain activity. Combined measurements investigating the effects of RA on both biomechanical and hemodynamic patterns might help for a better understanding of the neurophysiological mechanisms underlying gait and gait disorders as well as the effectiveness of robotic rehabilitation on motor recovery [37, 71]. Up to now, no consensus exists regarding how robotic devices should be designed, controlled or adjusted (i.e., device settings, such as the level of support) for synergistic interactions with the human body to achieve optimal neurorehabilitation [37, 72].…”
Section: Introductionmentioning
confidence: 99%
“…The sequelae post-TBI that affects cognitive function is known as postconcussive syndrome 24 . To minimize its impact in patient's quality of life, rehabilitation approaches that promote neuroplastic changes in the brain, such as those produced by exoskeleton training, could result in an overall increase in functional domains for the patient after a TBI or CVA 25 . While the overall improvement in cognitive FIM scores in the current cohort of patients was small, a 1 point increase in FIM scores corresponds to an increase of 1.08 more likely to be discharged to the home rather than to institutionalized care 26 ; hence decreasing healthcare cost on the long-term.…”
Section: Discussionmentioning
confidence: 99%
“…The use of robot-assisted gait training has been one of the most current studies in the field of rehabilitation, showing itself as a promising area [94][95][96][97]. In [98], the authors reported an initial study to analyze the emotion of patients, offering a therapist a better interpretation of the psychological state of the patient and their transition from each emotional state.…”
Section: Systems and Sensors In Physical Rehabilitationmentioning
confidence: 99%